The Applicability of A Tripartite Platformisation Definition: A Systematic Review - Shi, Shanshan (Technium Social Sciences Journal, 2025)
Introduction: This paper critically explores the broad application of the theoretical framework of platformisation. Platformisation is intricate and multidimensional, encompassing computational infrastructures, political economy, business studies, and cultural studies. Although existing research has addressed crucial gaps, an accurate definition is lacking. Methods: First, the paper examines the applications and definitions of platformisation from different academic perspectives. Second, the tripartite definition of platformisation (data infrastructures, markets, and governance) proposed by Poell et al. (2019) is scrutinized. Third, based on these three dimensions, this literature systematically compartmentalized existing research and evaluated the utility of the tripartite framework. Results: The review shows that although the tripartite framework provides a useful structure, it has certain limitations and is unable to adequately encompass numerous academic branches and theories. Simultaneously, with the rise of globalization, the framework must also address governance and policy challenges, incorporating intercultural perspectives into the analysis of platformisation Conclusion: To further academic understanding and provide insights for policymakers and stakeholders navigating the terrain of platformisation, addressing these gaps and determining an exact interdisciplinary and intercultural theorizing model will be essential. This study lays the groundwork for future inquiry and refinement of platformisation discourse in communication and internet research.